Peningkatan Kualitas Material Kayu Olahan Melalui Pendekatan Robust Design Taguchi dan Identifikasi Akar Masalah Melalui Fault Tree Analysis - Ice Trianiza; Agus Wiramsya Oscar; Irawan Noor; Abdurahim Sidiq (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to improve the quality of processed wood products through an integrative approach of Fault Tree Analysis (FTA) and the Taguchi Method. The use of FTA is focused on identifying the root causes of failure and the dominant factors affecting low product quality. Based on the fault tree analysis, it was found that the critical variables causing defects include cade room temperature, drying duration, and motor speed. Furthermore, Taguchi experiments were applied to determine the optimal process parameters to produce a robust product. The results showed that the optimal factor level combination was achieved at a cade room temperature of 65°C (level 2), a drying time of 18 days (level 1), and a motor speed of 2420 rpm (level 1). Statistical analysis through ANOVA indicates that the cade room temperature provides the most significant contribution to product quality at 45.69%. The application of these optimal parameters is projected to significantly reduce process variability, as the primary factors causing defects—specifically warping (48.5%) and uneven surfaces (32.5%)—have been successfully identified and controlled. Managerially, the company is recommended to implement the synergy of FTA and Taguchi methods as a continuous quality evaluation instrument. Additionally, a regular maintenance program for the cade room facility is crucial so that temperature fluctuations can be monitored precisely to guarantee consistent end-product quality.